Negative electrode material containing high-silicon carbon material, negative electrode plate, preparation method of negative electrode plate, lithium battery and electric equipment

By reasonably controlling the ratio of silicon-carbon composite materials, graphite, conductive agent and binder, a negative electrode sheet with high silicon content was prepared, which solved the problems of complex preparation process and high cost in traditional methods, and achieved high energy density and good quality cyclic stability.

CN119419216APending Publication Date: 2025-02-11SHENZHEN BAK POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411542406.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the traditional negative electrode sheet preparation method, the preparation process of silicon carbon materials is complex, which limits the electrochemical performance of the negative electrode sheet and increases production costs, making it difficult to meet the market demand for negative electrode sheets with high silicon content and excellent performance.

Method used

High silicon carbon composite materials are used as the negative electrode active material, and a negative electrode sheet with high silicon content is prepared by reasonably controlling the proportion of silicon carbon composite materials, graphite, conductive agent and binder. The method includes mixing the silicon-carbon composite material with graphite, adding solvent, binder and conductive agent, and after stirring and adjusting the viscosity, forming a negative electrode slurry, coating on the negative electrode current collector, and drying and compacting to obtain the negative electrode piece.

Benefits of technology

It improves the energy density of the negative electrode sheet, improves its electrochemical performance and cycle stability, simplifies the preparation process, reduces production costs, and has broad market application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419216A_ABST
    Figure CN119419216A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material containing a high-silicon carbon material, a negative electrode pole piece, a preparation method of the negative electrode pole piece, a lithium battery and electric equipment, and relates to the field of lithium batteries. The negative electrode material containing the high silicon carbon material comprises the following raw materials: a silicon carbon composite material, a conductive agent and a binder, the silicon content in the silicon carbon composite material is 30-50 wt%, and the mass ratio of the silicon carbon composite material to graphite to the conductive agent to the binder is (20-60): (30-70): (10-20): (5-10). By reasonably controlling the dosage ratio of the silicon-carbon composite material, the graphite, the conductive agent and the binder, the proportion of the raw materials can be matched with that of the silicon-carbon composite material with high silicon content, so that the electrical property of the negative electrode active material can be remarkably improved, and the overall performance of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium batteries, and in particular to a negative electrode plate containing high silicon-carbon material and a preparation method thereof, a lithium battery, and electrical equipment. Background Art

[0002] With the global pursuit of clean energy and sustainable development, the rapid development of electric vehicles, wearable devices and large-scale energy storage systems has placed increasingly stringent performance requirements on lithium-ion batteries.

[0003] The energy density, cycle life and safety performance of lithium-ion batteries have become the key to their technological innovation. Silicon-carbon composite materials have become a popular choice for the next generation of negative electrode materials due to their high specific capacity and excellent cycle performance. However, in the traditional method of preparing negative electrode sheets, the preparation process of silicon-carbon materials is complicated, which not only limits the electrochemical performance of the negative electrode sheets, but also increases the production cost. Therefore, the development of a simple and efficient method for preparing negative electrode sheets with high silicon content and excellent performance is of great significance to meet market demand and promote the advancement of lithium-ion battery technology. Summary of the invention

[0004] The purpose of this application is to provide a negative electrode material containing high silicon carbon material, a negative electrode plate and a preparation method thereof, a lithium battery, and electrical equipment to solve the above-mentioned problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A negative electrode material containing high silicon-carbon material, wherein the raw materials include a silicon-carbon composite material, a conductive agent, and a binder. The silicon content in the silicon-carbon composite material is 30-50wt%, and the mass ratio of the silicon-carbon composite material, the graphite, the conductive agent, and the binder is (20-60): (30-70): (10-20): (5-10).

[0007] Optionally, the graphite includes natural graphite and artificial graphite.

[0008] Optionally, the conductive agent includes one or more of carbon black, graphene, and carbon nanotubes.

[0009] Optionally, the binder includes one or more of polyvinylidene fluoride, styrene-butadiene rubber, and carboxymethyl cellulose.

[0010] The present application also provides a negative electrode plate containing high silicon-carbon material, and the raw materials of the negative electrode plate containing high silicon-carbon material include negative electrode materials containing high silicon-carbon material.

[0011] Optionally, the thickness of the active layer of the negative electrode sheet is 50-200 μm, and the compaction density of the active layer of the negative electrode sheet is 1-1.6 g / cm3 .

[0012] The present application also provides a method for preparing a negative electrode sheet containing a high silicon carbon material, the preparation method comprising:

[0013] Mixing the negative electrode material with a solvent and adjusting the viscosity of the slurry to obtain a negative electrode slurry;

[0014] The negative electrode slurry is coated on the negative electrode current collector, and after drying and compacting, the negative electrode sheet containing the high silicon-carbon material is obtained.

[0015] Optionally, the preparation process of the negative electrode slurry includes:

[0016] The silicon-carbon composite material and graphite are first mixed to obtain a first mixture;

[0017] A solvent, a binder and a conductive agent are mixed to obtain a glue solution. Taking the mass of the glue solution as 100%, 30-35% of the glue solution is mixed with the first mixture for a second time to obtain a second mixture; 30-35% of the glue solution is mixed with the second mixture for a third time to obtain a third mixture; 30-35% of the glue solution is mixed with the third mixture for a fourth time to obtain a fourth mixture; and the viscosity of the fourth mixture is adjusted to obtain the negative electrode slurry.

[0018] Optionally, the solvent includes N-methylpyrrolidone, water, and ethylene glycol.

[0019] Optionally, the added amount of the solvent is 70-100% of the total mass of the raw materials.

[0020] Optionally, the viscosity is 1900-2200 mPa·s.

[0021] Optionally, the method for preparing the glue solution includes: mixing the binder with 30-35% of the solvent, based on the mass of the solvent itself as 100%, at a speed of 1300-1600 rpm for 50-70 min; adding a conductive agent and mixing with the remaining solvent at a speed of 1300-1600 rpm for 50-70 min;

[0022] Optionally, during the first mixing process, the rotation speed is 5-30rpm and the time is 50-70min; during the second mixing process, the rotation speed is 450-700rpm and the time is 50-70min; during the third mixing process, the rotation speed is 750-900rpm and the time is 50-70min; during the fourth mixing process, the rotation speed is 1300-1600rpm and the time is 80-100min.

[0023] Optionally, the method for preparing the negative electrode sheet containing high silicon carbon material further comprises post-treatment, and the post-treatment comprises heat treatment or surface modification;

[0024] During the heat treatment, the heating rate is 3-10°C / min at normal pressure, the temperature is raised to 100-150°C, and the treatment time is 1-2h;

[0025] During the surface modification process, the reaction gas includes methane and hydrogen, the gas flow rate is 115-125 ml / min, the temperature is raised to 400-650° C. under normal pressure, and the treatment time is 5-30 min.

[0026] The present application also provides a lithium-ion battery, the raw materials of which include the negative electrode plate containing the high silicon-carbon material.

[0027] An electrical device comprises the lithium-ion battery.

[0028] Compared with the prior art, the beneficial effects of this application include:

[0029] The present application provides a negative electrode sheet containing high silicon-carbon material. In the negative electrode material, by reasonably controlling the proportion of silicon-carbon composite material, graphite, conductive agent, and binder, the proportion of raw materials can be adapted to the silicon-carbon composite material with high silicon content; at the same time, the use of silicon-carbon composite material with high silicon content as the negative electrode active material can effectively improve the specific capacity of the negative electrode active material, thereby significantly improving the energy density of the battery. At the same time, the silicon-carbon composite material will undergo significant volume expansion during the charging and discharging process, resulting in a decrease in battery performance. Therefore, combined with the buffering effect of graphite, the volume expansion of silicon can be effectively inhibited and the cycle life of the battery can be extended. The conductive agent can further synergize with the silicon-carbon composite material, improve the conductivity of the negative electrode active material, reduce the internal resistance, and thus improve the current transmission efficiency, thereby improving the output power of the battery and optimizing the electrical performance of the battery. In addition, by reasonably controlling the proportion of the components of the negative electrode slurry, it can ensure that the battery maintains a high capacity and stability during fast charging, avoiding rapid attenuation of battery performance.

[0030] The method for preparing the negative electrode sheet containing high silicon carbon material provided in the present application significantly improves the energy density of the negative electrode sheet, improves its electrochemical performance and cycle stability, and provides strong support for the development of high-performance lithium-ion batteries. At the same time, the method simplifies the preparation process, improves production efficiency, reduces production costs, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0032] Figure 1 This is a physical picture of the negative electrode plate containing high silicon carbon material prepared in Example 1. DETAILED DESCRIPTION

[0033] The present application provides a negative electrode material containing high silicon carbon material, a negative electrode sheet and a preparation method thereof, a lithium battery, and electrical equipment. In order to better explain the technical solution provided by the present application, before the embodiments, the technical solution is first described as a whole, as follows:

[0034] In the first aspect, the present application provides a negative electrode material containing a high silicon-carbon material, wherein the raw materials include a silicon-carbon composite material, a conductive agent, and a binder. The silicon content in the silicon-carbon composite material is 30-50wt%, and the mass ratio of the silicon-carbon composite material, the graphite, the conductive agent, and the binder is (20-60): (30-70): (10-20): (5-10).

[0035] Optionally, the silicon content in the silicon-carbon composite material may be 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, 50wt%, or any value between 30-50wt%. The mass ratio of the silicon-carbon composite material, the graphite, the conductive agent, and the binder may be any value or any interval between (20-60): (30-70): (10-20): (5-10).

[0036] In an optional embodiment, the graphite includes natural graphite and artificial graphite.

[0037] In an optional embodiment, the conductive agent includes one or more of carbon black, graphene, and carbon nanotubes.

[0038] In an optional embodiment, the binder includes one or more of polyvinylidene fluoride, styrene-butadiene rubber, and carboxymethyl cellulose.

[0039] In a second aspect, the present application also provides a negative electrode plate containing a high silicon-carbon material, wherein the raw materials of the negative electrode plate containing a high silicon-carbon material include a negative electrode material containing a high silicon-carbon material.

[0040] In an optional embodiment, the thickness of the active layer of the negative electrode plate is 50-200 μm, and the compaction density of the active layer of the negative electrode plate is 1-1.6 g / cm3 By precisely controlling the coating thickness, the thermal stability of the battery during the charge and discharge process can be ensured, thereby improving the safety of the battery; compaction density is one of the key indicators for evaluating the performance of negative electrode materials, which directly affects the capacity, energy density and cycle life of the battery. By testing and optimizing the compaction density, the compaction degree of the negative electrode material can be understood, and then the material formula and production process can be optimized to improve the capacity and energy density of the battery.

[0041] Optionally, the thickness of the negative electrode active layer may be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, or any value between 50 and 200 μm; the compaction density of the negative electrode may be 1 g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , or 1-1.6g / cm 3 Any value in between.

[0042] The present application also provides a method for preparing a negative electrode sheet containing a high silicon carbon material, the preparation method comprising:

[0043] Mixing the negative electrode material with a solvent and adjusting the viscosity of the slurry to obtain a negative electrode slurry;

[0044] The negative electrode slurry is coated on the negative electrode current collector, and after drying and compacting, the negative electrode sheet containing the high silicon-carbon material is obtained.

[0045] In an optional embodiment, the preparation process of the negative electrode slurry includes:

[0046] The silicon-carbon composite material and graphite are first mixed to obtain a first mixture;

[0047] A solvent, a binder and a conductive agent are mixed to obtain a glue solution. Taking the mass of the glue solution as 100%, 30-35% of the glue solution is mixed with the first mixture for a second time to obtain a second mixture; 30-35% of the glue solution is mixed with the second mixture for a third time to obtain a third mixture; 30-35% of the glue solution is mixed with the third mixture for a fourth time to obtain a fourth mixture; and the viscosity of the fourth mixture is adjusted to obtain the negative electrode slurry.

[0048] In an optional embodiment, the solvent includes N-methylpyrrolidone, water, and ethylene glycol.

[0049] In an optional embodiment, the amount of the solvent added is 70-100% of the total mass of the raw materials. Under this amount of solvent added, the fluidity of the prepared negative electrode slurry can be ensured, and the negative electrode slurry can be guaranteed to have a certain viscosity, enhance the coating property, and facilitate the formation of a stable coating.

[0050] Optionally, the added amount of the solvent can be 70%, 75%, 80%, 85%, 90%, 95%, 100% of the total mass of the raw materials, or any value between 70-100% of the total mass of the raw materials.

[0051] In an optional embodiment, the viscosity is 1900-2200 mPa·s. At this viscosity, it can be ensured that the components such as active materials, conductive agents and adhesives in the slurry are evenly dispersed to form a stable electrode structure. If the viscosity is too high, the fluidity of the slurry will deteriorate, and it will be difficult to evenly coat the electrode sheet, which may cause uneven thickness and uneven surface of the electrode sheet, thereby affecting the charge and discharge performance and cycle life of the battery. On the contrary, if the viscosity is too low, the slurry may be too thin to form a stable coating, which will also affect the performance of the battery.

[0052] Optionally, the viscosity of the negative electrode slurry may be 1900 mPa·s, 1950 mPa·s, 2000 mPa·s, 2050 mPa·s, 2100 mPa·s, 2150 mPa·s, 2200 mPa·s, or any value between 1900 and 2200 mPa·s.

[0053] In an optional embodiment, the method for preparing the glue solution includes: mixing the binder with 30-35% of the solvent, based on the mass of the solvent itself as 100%, at a speed of 1300-1600 rpm for 50-70 min; adding a conductive agent and mixing with the remaining solvent at a speed of 1300-1600 rpm for 50-70 min;

[0054] Optionally, when the binder is mixed with 30-35% of the solvent, the rotation speed can be 1300rpm, 1400rpm, 1500rpm, 1600rpm, or any value between 1300-1600rpm; when the conductive agent is mixed with the remaining solvent, the rotation speed can be 1300rpm, 1400rpm, 1500rpm, 1600rpm, or any value between 1300-1600rpm.

[0055] In an optional embodiment, during the first mixing process, the rotation speed is 5-30rpm, and the time is 50-70min; during the second mixing process, the rotation speed is 450-700rpm, and the time is 50-70min; during the third mixing process, the rotation speed is 750-900rpm, and the time is 50-70min; during the fourth mixing process, the rotation speed is 1300-1600rpm, and the time is 80-100min.

[0056] Optionally, during the first mixing process, the rotation speed may be 5rpm, 10rpm, 15rpm, 20rpm, 25rpm, 30rpm, or any value between 5-30rpm; the first mixing time may be 50min, 55min, 60min, 70min, or any value between 50-70min. During the second mixing process, the rotation speed may be 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, or any value between 450-700rpm; the second mixing time may be 50min, 55min, 60min, 65min, 70min, or any value between 50-70min. During the third mixing process, the rotation speed may be 750rpm, 800rpm, 850rpm, 900rpm, or any value between 750-900rpm; the third mixing time may be 50min, 55min, 60min, 65min, 70min, or any value between 50-70min. The rotation speed of the fourth mixing may be 1300rpm, 1350rpm, 1400rpm, 1450rpm, 1500rpm, 1550rpm, 1600rpm, or any value between 1300-1600rpm; the time of the fourth mixing may be 80min, 85min, 90min, 95min, 100min, or any value between 80-100min.

[0057] In an optional embodiment, the method for preparing the negative electrode plate containing high silicon carbon material further includes post-treatment, and the post-treatment includes heat treatment or surface modification.

[0058] During the heat treatment, the heating rate is 3-10°C / min at normal pressure, the temperature is raised to 100-150°C, and the treatment time is 1-2h. Heat treatment can cause changes in the microstructure inside the electrode material, such as grain growth, phase change, etc., thereby optimizing the performance of the material. For negative electrode materials, appropriate heat treatment can improve their conductivity and ion diffusion rate, which is beneficial to improving battery performance.

[0059] Optionally, the heating rate under normal pressure can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any value between 3-10°C / min. The end point of the heating can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or any value between 100-150°C. The treatment time can be 1h, 2h, or any value between 1-2h.

[0060] During the surface modification process, the reaction gas includes methane and hydrogen, the gas flow rate is 115-125 ml / min, the temperature is raised to 570°C under normal pressure, and the treatment time is 15 minutes. This process reduces the surface defects of the electrode, makes the current distribution more uniform, averages the lithium ion diffusion time, and improves the cycle stability of the electrode.

[0061] The present application also provides a lithium-ion battery, the raw materials of which include the negative electrode plate containing the high silicon-carbon material.

[0062] An electrical device comprises the lithium-ion battery.

[0063] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0064] Example 1

[0065] This embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0066] Commercially available silicon-carbon composite materials with a silicon content of 40wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 23:57:15:5.

[0067] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0068] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2200mPa·s.

[0069] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 110μm, and then controlling the temperature to dry at 110℃ for 3min, and then rolling the electrode to a compaction density of 1.55g / cm 3 .

[0070] The negative electrode sheet after forming is surface modified, and a thin carbon layer is coated on the surface of the negative electrode sheet by chemical vapor deposition. The gas uses methane gas with a high carbon content, hydrogen to promote reaction and hydrogen to remove impurities, the flow rate is controlled at 120ml / min, and the coating temperature gradient is controlled to rise to 570℃ under normal pressure for 15min to obtain a negative electrode sheet containing high silicon carbon material, such as Figure 1 shown.

[0071] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0072] Example 2

[0073] This embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0074] Commercially available silicon-carbon composite materials with a silicon content of 35wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 23:57:15:5.

[0075] The mass ratio of the solvent to the raw material is 73:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0076] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2200mPa·s.

[0077] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 116μm, and then controlling the temperature to dry at 80℃ for 4min, and then rolling the electrode to a compaction density of 1.45g / cm 3 .

[0078] The negative electrode sheet after forming is surface modified, and a thin carbon layer is coated on the surface of the negative electrode sheet using chemical vapor deposition. The gas uses methane gas with a high carbon content, hydrogen to promote reaction and hydrogen to remove impurities, the flow rate is controlled at 120ml / min, and the coating temperature gradient is controlled to rise to 570℃ under normal pressure for 15min to obtain a negative electrode sheet containing high silicon-carbon material.

[0079] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0080] Example 3

[0081] This embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0082] Commercially available silicon-carbon composite materials with a silicon content of 50wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 20:60:15:5.

[0083] The mass ratio of the solvent to the raw material is 95:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0084] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2200mPa·s.

[0085] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 116μm, and then controlling the temperature to dry at 115℃ for 4min, and then rolling the electrode to a compaction density of 1.45g / cm 3 .

[0086] The electrochemical performance of the negative electrode sheet after forming is improved by surface modification, and a thin carbon layer is coated on the surface of the negative electrode sheet by chemical vapor deposition. The gas uses methane gas with a high carbon content, hydrogen to promote reaction and hydrogen to remove impurities, the flow rate is controlled at 120ml / min, and the coating temperature gradient is controlled to rise to 570℃ under normal pressure for 15min to obtain a negative electrode sheet containing high silicon-carbon material.

[0087] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0088] Example 4

[0089] This embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0090] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0091] The mass ratio of the solvent to the raw material is 70:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0092] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0093] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 100 μm, and then controlling the temperature to dry at 120 ° C for 4 minutes, and then rolling the electrode to a compaction density of 1.50 g / cm 3 .

[0094] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0095] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0096] Example 5

[0097] This embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0098] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0099] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0100] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0101] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0102] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 100 μm, and then controlling the temperature to dry at 120 ° C for 4 minutes, and then rolling the electrode to a compaction density of 1.50 g / cm 3 .

[0103] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0104] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0105] Example 6

[0106] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0107] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0108] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0109] The mass ratio of the solvent to the raw material is 90:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0110] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0111] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 100 μm, and then controlling the temperature to dry at 120 ° C for 4 minutes, and then rolling the electrode to a compaction density of 1.50 g / cm 3 .

[0112] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0113] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0114] Example 7

[0115] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0116] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0117] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0118] The mass ratio of the solvent to the raw material is 100:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0119] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0120] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 100 μm, and then controlling the temperature to dry at 120 ° C for 4 minutes, and then rolling the electrode to a compaction density of 1.50 g / cm 3 .

[0121] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0122] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0123] Example 8

[0124] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0125] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0126] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0127] The mass ratio of the solvent to the raw material is 70:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0128] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0129] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 50μm, and then controlling the temperature to dry at 120℃ for 4min, and then rolling the electrode to a compaction density of 1.50g / cm 3 .

[0130] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0131] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0132] Example 9

[0133] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0134] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0135] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0136] The mass ratio of the solvent to the raw material is 70:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0137] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0138] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 120℃ for 4min, and then rolling the electrode to a compaction density of 1.50g / cm 3 .

[0139] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0140] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0141] Example 10

[0142] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0143] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0144] Commercially available silicon-carbon composite materials with a silicon content of 30wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 25:50:15:10.

[0145] The mass ratio of the solvent to the raw material is 70:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0146] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2500mPa·s.

[0147] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 200 μm, and then controlling the temperature to dry at 120 ° C for 4 minutes, and then rolling the electrode to a compaction density of 1.50 g / cm 3 .

[0148] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0149] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0150] Embodiment 11

[0151] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0152] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0153] Commercially available silicon-carbon composite materials with a silicon content of 45wt% and natural graphite were selected as negative electrode active materials, while carbon black and carbon nanotubes (2:1) were used as conductive agents, polyvinylidene fluoride and styrene-butadiene rubber (1:1) were used as binders, and water was used as solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder was 30:50:10:10.

[0154] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0155] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2300mPa·s.

[0156] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 90℃ for 5min, and then rolling the electrode to a compaction density of 1.20g / cm 3 .

[0157] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0158] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0159] Example 12

[0160] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0161] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0162] Commercially available silicon-carbon composite materials with a silicon content of 45wt% and natural graphite were selected as negative electrode active materials, while carbon black and carbon nanotubes (2:1) were used as conductive agents, polyvinylidene fluoride and styrene-butadiene rubber (1:1) were used as binders, and water was used as solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder was 30:50:10:10.

[0163] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0164] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2300mPa·s.

[0165] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 90℃ for 5min, and then rolling the electrode to a compaction density of 1.20g / cm 3 .

[0166] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 130°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0167] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0168] Embodiment 13

[0169] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0170] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0171] Commercially available silicon-carbon composite materials with a silicon content of 45wt% and natural graphite were selected as negative electrode active materials, while carbon black and carbon nanotubes (2:1) were used as conductive agents, polyvinylidene fluoride and styrene-butadiene rubber (1:1) were used as binders, and water was used as solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder was 30:50:10:10.

[0172] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0173] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2300mPa·s.

[0174] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 90℃ for 5min, and then rolling the electrode to a compaction density of 1.20g / cm 3 .

[0175] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 150°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0176] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0177] Embodiment 14

[0178] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0179] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0180] Commercially available silicon-carbon composite materials with a silicon content of 45wt% and natural graphite were selected as negative electrode active materials, while carbon black and carbon nanotubes (2:1) were used as conductive agents, polyvinylidene fluoride and styrene-butadiene rubber (1:1) were used as binders, and water was used as solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder was 30:50:10:10.

[0181] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0182] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2300mPa·s.

[0183] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 90℃ for 5min, and then rolling the electrode to a compaction density of 1.0g / cm 3 .

[0184] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0185] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0186] Embodiment 15

[0187] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0188] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0189] Commercially available silicon-carbon composite materials with a silicon content of 45wt% and natural graphite were selected as negative electrode active materials, while carbon black and carbon nanotubes (2:1) were used as conductive agents, polyvinylidene fluoride and styrene-butadiene rubber (1:1) were used as binders, and water was used as solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder was 30:50:10:10.

[0190] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0191] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2300mPa·s.

[0192] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 90℃ for 5min, and then rolling the electrode to a compaction density of 1.4g / cm 3 .

[0193] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0194] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0195] Example 16

[0196] The embodiment provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0197] This embodiment provides a negative electrode sheet containing a high silicon carbon material, and the preparation method is as follows:

[0198] Commercially available silicon-carbon composite materials with a silicon content of 45wt% and natural graphite were selected as negative electrode active materials, while carbon black and carbon nanotubes (2:1) were used as conductive agents, polyvinylidene fluoride and styrene-butadiene rubber (1:1) were used as binders, and water was used as solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder was 30:50:10:10.

[0199] The mass ratio of the solvent to the raw material is 80:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0200] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2300mPa·s.

[0201] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 150μm, and then controlling the temperature to dry at 90℃ for 5min, and then rolling the electrode to a compaction density of 1.6g / cm 3 .

[0202] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet containing high silicon-carbon material.

[0203] This embodiment also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0204] Comparative Example 1

[0205] This comparative example provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0206] Commercially available silicon-carbon composite materials with a silicon content of 50wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 20:60:15:5.

[0207] The mass ratio of the solvent to the raw material is 95:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0208] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2200mPa·s.

[0209] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 116μm, and then controlling the temperature to dry at 115℃ for 4min, and then rolling the electrode to a compaction density of 1.45g / cm 3 , and obtain a negative electrode sheet.

[0210] This comparative example also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0211] Comparative Example 2

[0212] This comparative example provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0213] Commercially available silicon-carbon composite materials with a silicon content of 10 wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 20:60:15:5.

[0214] The mass ratio of the solvent to the raw material is 95:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0215] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2200mPa·s.

[0216] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 116μm, and then controlling the temperature to dry at 115℃ for 4min, and then rolling the electrode to a compaction density of 1.45g / cm 3 .

[0217] The electrochemical performance of the negative electrode sheet after forming is improved by surface modification, and a thin carbon layer is coated on the surface of the negative electrode sheet by chemical vapor deposition. The gas uses methane gas with a high carbon content, hydrogen to promote reaction and hydrogen to remove impurities, the flow rate is controlled at 120ml / min, and the coating temperature gradient is controlled to rise to 570℃ under normal pressure for 15min to obtain a negative electrode sheet.

[0218] This comparative example also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0219] Comparative Example 3

[0220] This comparative example provides a negative electrode material and a negative electrode plate containing a high silicon carbon material, and the preparation method is as follows:

[0221] Commercially available silicon-carbon composite materials with a silicon content of 8wt% and artificial graphite are selected as negative electrode active materials, while graphene is used as a conductive agent, styrene-butadiene rubber is used as a binder, and water is used as a solvent. The mass ratio of silicon-carbon composite materials, graphite, conductive agent and binder is 20:60:15:5.

[0222] The mass ratio of the solvent to the raw material is 95:100. Taking the mass of the solvent itself as 100%, 30% of the solvent is first added and stirred at 1500 rpm for 60 minutes; then the conductive agent and the remaining 70% of the solvent are added and stirred for 90 minutes to obtain a glue solution.

[0223] The slurry preparation process is as follows: first, the silicon-carbon composite material and graphite are dry-mixed and stirred at 15rpm for 60min; based on the mass of the glue liquid itself as 100%, 35% of the glue liquid is first added and stirred at 600rpm for 60min; then 35% of the glue liquid is added and stirred at 800rpm for 60min, and finally the remaining 30% of the glue liquid is added and stirred at 1500rpm for 90min; the slurry viscosity is adjusted to 2200mPa·s.

[0224] The coating process uses extrusion coating to coat the slurry on the copper foil, controlling the coating thickness to 116μm, and then controlling the temperature to dry at 115℃ for 4min, and then rolling the electrode to a compaction density of 1.45g / cm3 .

[0225] Finally, the formed negative electrode sheet was heat treated at a heating rate of 5°C / min, a final temperature of 120°C, and a treatment time of 2h to improve its electrochemical performance and cycle stability. After the above steps, a negative electrode sheet containing high silicon-carbon material was successfully prepared to obtain a negative electrode sheet.

[0226] This comparative example also provides a lithium-ion battery, whose raw materials include the above-mentioned negative electrode plate containing high silicon-carbon material, the positive electrode material is lithium nickel cobalt manganese oxide (Li(Ni8Co1Mn1)O2), the electrolyte is 1MLiPF6 (EC:EMC:DMC (11:34:55)), the diaphragm is a PP diaphragm with a thickness of 11μm, and the other steps are assembled according to the conventional method to finally prepare a lithium-ion battery.

[0227] Experimental example

[0228] The lithium-ion battery containing the negative electrode sheet with high carbon-silicon content prepared in Examples 1-3 was subjected to electrochemical testing, and the results are shown in Table 1:

[0229] Table 1: Electrochemical properties of the electrode

[0230]

[0231] It can be seen that the content and mass ratio of silicon-carbon composite materials in lithium-ion batteries have a great influence on the first discharge capacity of the battery. Example 1 with a silicon content of 40wt% and a mass ratio of 23 has a higher first discharge capacity. At the same time, the solvent ratio, coating thickness and compaction density will affect the battery cycle performance. The solvent, coating thickness and compaction density will also change according to the different ratios of the battery system. Further exploration of the rules is reflected in the following examples.

[0232] Electrochemical tests were performed on the lithium-ion batteries containing negative electrode sheets with high carbon-silicon content prepared in Examples 4-7 to explore the effect of the solvent ratio on the fluidity of the negative electrode slurry and the cycle performance. The results are shown in Table 2:

[0233] Table 2: Effect of solvent ratio on fluidity and cycle performance

[0234]

[0235] It can be seen that the solvent ratio in Examples 4-7 increases (70, 80, 90, 100). By comparing the slurry fluidity and cycle performance, it can be found that when the solvent ratio is low, the slurry fluidity is low and the cycle performance is also poor; too high a solvent ratio will lead to too high slurry fluidity and poor cycle performance. A moderate solvent ratio can improve the cycle performance.

[0236] Electrochemical tests were performed on the lithium-ion batteries containing negative electrode sheets with high carbon-silicon content prepared in Examples 4 and 8-10 to explore the effect of the coating thickness of the active layer on the electrochemical performance. The results are shown in Table 3:

[0237] Table 3: Effect of coating thickness on electrochemical performance

[0238]

[0239] It can be seen that the coating thickness in Examples 4, 8-10 is (100, 50, 150, 200 μm), respectively. The first discharge capacity increases with the increase of coating thickness. As for the cycle performance, if the coating thickness is too high, the lithium ions will be aggregated on the negative electrode surface due to the long transmission path during the charging process, resulting in poor cycle performance. However, if the coating thickness is too low, the drying temperature during the coating process will cause the electrode to dry out and crack, resulting in poor cycle performance.

[0240] Electrochemical tests were performed on the lithium-ion batteries containing negative electrode sheets with high carbon-silicon content prepared in Examples 11-13 to explore the effect of heat treatment temperature on the performance of the electrode sheets. The results are shown in Table 4:

[0241] Table 4: Effect of heat treatment temperature on pole piece performance

[0242]

[0243] It can be seen that the heat treatment temperature of Examples 11-13 gradually increases (120, 130, 150°C). As the heat treatment temperature increases, impurities on the electrode surface are removed, increasing the number of active sites on the electrode surface, improving the first discharge capacity, and also improving the battery cycle performance.

[0244] Electrochemical tests were performed on lithium-ion batteries containing negative electrode sheets with high carbon-silicon content prepared in Example 11 and Examples 14-16 to explore the effect of the compaction density of the electrode sheet on the performance of the electrode sheet. The results are shown in Table 5:

[0245] Table 5: Effect of electrode compaction density on electrochemical performance

[0246]

[0247] It can be seen that the compaction density of Examples 11, 14-16 gradually increases, and the first charge capacity and cycle performance first increase and then decrease. When the compaction density is low, the pole piece will be loose, the active material will not be fully contacted, the battery contact internal resistance will increase, and the first charge capacity and cycle performance will deteriorate. However, high compaction density will lead to a decrease in the pole piece porosity, and even cause the active material particles to be squeezed and pulverized, which will deteriorate the first discharge capacity and cycle performance of the battery.

[0248] Electrochemical tests were performed on lithium-ion batteries containing negative electrode sheets with high carbon-silicon content prepared in Example 3 and Comparative Examples 1-3 to explore the effect of post-treatment on the performance of the electrode sheets. The results are shown in Table 6:

[0249] Table 6: Comparison of post-treatment on electrode cycle performance

[0250]

[0251]

[0252] It can be seen that the 50wt% silicon-carbon content in Example 3 is much higher than the 10wt% and 8wt% silicon-carbon material gram capacity in Comparative Examples 2 and 3. By comparing the results of Example 3 and Comparative Example 1, it can be seen that the capacity of the negative electrode plate after post-treatment is slightly higher and the cycle performance is slightly better, indicating that post-treatment is beneficial to improving the capacity and cycle performance of the plate.

[0253] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0254] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A negative electrode material containing a high silicon carbon material, characterized in that: The raw materials include silicon-carbon composite material, graphite, conductive agent and binder. The silicon content in the silicon-carbon composite material is 30-50wt%. The mass ratio of the silicon-carbon composite material, the graphite, the conductive agent and the binder is (20-60): (30-70): (10-20): (5-10).

2. The negative electrode material containing high silicon carbon material according to claim 1, characterized in that: At least one of the following conditions is met: a. The graphite includes natural graphite and artificial graphite; b. The conductive agent includes one or more of carbon black, graphene, and carbon nanotubes; c. The binder includes one or more of polyvinylidene fluoride, styrene-butadiene rubber, and carboxymethyl cellulose.

3. A negative electrode sheet containing high silicon carbon material, characterized in that: The raw material of the negative electrode plate containing high silicon-carbon material includes the negative electrode material containing high silicon-carbon material according to any one of claims 1-2.

4. The negative electrode sheet containing high silicon carbon material according to claim 3, characterized in that: The thickness of the active layer of the negative electrode sheet is 50-200 μm, and the compaction density of the active layer of the negative electrode sheet is 1-1.6 g / cm 3 .

5. A method for preparing a negative electrode sheet containing a high silicon carbon material according to claim 3 or 4, characterized in that: include: Mixing the negative electrode material with a solvent and adjusting the viscosity of the slurry to obtain a negative electrode slurry; The negative electrode slurry is coated on the negative electrode current collector, and after drying and compacting, the negative electrode sheet containing the high silicon-carbon material is obtained.

6. The method for preparing a negative electrode sheet containing a high silicon carbon material according to claim 5, characterized in that: At least one of the following conditions is met: d. The preparation process of the negative electrode slurry includes: first mixing the silicon-carbon composite material with graphite to obtain a first mixture; mixing a solvent, a binder, and a conductive agent to obtain a glue solution, and second mixing 30-35% of the glue solution with the first mixture to obtain a second mixture based on the mass of the glue solution itself as 100%; third mixing 30-35% of the glue solution with the second mixture to obtain a third mixture; fourth mixing 30-35% of the glue solution with the third mixture to obtain a fourth mixture; adjusting the viscosity of the fourth mixture to obtain the negative electrode slurry; e. The solvent includes N-methylpyrrolidone, water, and ethylene glycol; f. The amount of the solvent added is 70-100% of the total mass of the raw material; g. The viscosity is 1900-2200 mPa·s.

7. The method for preparing a negative electrode sheet containing a high silicon carbon material according to claim 6, characterized in that: At least one of the following conditions is met: h. The method for preparing the glue solution comprises mixing the binder with 30-35% of the solvent, based on the mass of the solvent itself as 100%, at a speed of 1300-1600rpm for 50-70min; adding a conductive agent and mixing with the remaining solvent at a speed of 1300-1600rpm for 80-100min; i. During the first mixing process, the speed is 5-30rpm and the time is 50-70min; j. During the second mixing process, the speed is 450-700rpm and the time is 50-70min; k. During the third mixing process, the speed is 750-900rpm and the time is 50-70min; l. During the fourth mixing process, the rotation speed is 1300-1600rpm and the time is 80-100min.

8. The method for preparing a negative electrode sheet containing a high silicon carbon material according to claim 5, characterized in that: The method for preparing the negative electrode sheet containing high silicon carbon material also includes post-processing, and the post-processing includes heat treatment or surface modification; During the heat treatment, the heating rate is 3-10°C / min at normal pressure, the temperature is raised to 100-150°C, and the treatment time is 1-2h; During the surface modification process, the reaction gas includes methane and hydrogen, the gas flow rate is 115-125 ml / min, the temperature is raised to 400-650° C. under normal pressure, and the treatment time is 5-30 min.

9. A lithium ion battery, characterized in that: The raw materials include the negative electrode sheet containing high silicon carbon material as described in claim 3 or 4.

10. An electrical equipment, characterized in that: A lithium-ion battery comprising the lithium-ion battery of claim 9.